2018
DOI: 10.1111/bjh.15076
|View full text |Cite
|
Sign up to set email alerts
|

Aeroallergen sensitization predicts acute chest syndrome in children with sickle cell anaemia

Abstract: Asthma is associated with higher rates of acute chest syndrome (ACS) and vaso-occlusive pain episodes among children with sickle cell anaemia (SCA). Aeroallergen sensitization is a risk factor for asthma. We hypothesized that aeroallergen sensitization is associated with an increased incidence of hospitalizations for ACS and pain. Participants in a multicentre, longitudinal cohort study, aged 4-18 years with SCA, underwent skin prick testing to ten aeroallergens. ACS and pain episodes were collected from birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While some microorganisms are particularly virulent because of the functional asplenia that develops in infancy in sickle cell anemia, the lung, in general, is more vulnerable to infection in children with SCD. Bronchial hyper-reactivity, asthma, and chronic airway inflammation (209) are highly prevalent in children with SCD and may result in a proinflammatory milieu that amplifies cellular and humoral immunity to airway pathogens, thus leading to a paroxysmal, detrimental response (210,211).…”
Section: Convergence Of Multiple Pathogenic Pathways: Acute Chest Syndromementioning
confidence: 99%
“…While some microorganisms are particularly virulent because of the functional asplenia that develops in infancy in sickle cell anemia, the lung, in general, is more vulnerable to infection in children with SCD. Bronchial hyper-reactivity, asthma, and chronic airway inflammation (209) are highly prevalent in children with SCD and may result in a proinflammatory milieu that amplifies cellular and humoral immunity to airway pathogens, thus leading to a paroxysmal, detrimental response (210,211).…”
Section: Convergence Of Multiple Pathogenic Pathways: Acute Chest Syndromementioning
confidence: 99%
“…In contrast, other studies have found significant associations between elevated IgE levels and a diagnosis of asthma in patients with SCD . Further, high IgE levels and aeroallergen sensitization in patients with SCD have been reported as risk factors for ACS episodes . The relationship between atopy and SCD needs to be further understood.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, recurrent episodes of ACS can lead to the development of debilitating chronic lung disease. 76 Several risk factors such as young age, low HbF, high baseline hemoglobin, steady-state leukocytosis, 74 asthma/ airway hyperresponsiveness, 77 and aeroallergen sensitization 78 have been associated with the development ACS. ACS is an ideal target for biomarker development, as two-thirds of ACS episodes occur in patients who are hospitalized for other reasons (primarily VOCs).…”
Section: Acs and Multiorgan Failure Syndrome (Mofs)mentioning
confidence: 99%